2009
DOI: 10.1111/j.1749-6632.2009.04674.x
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine Revisited

Abstract: Purified from a Mediterranean plant nearly two centuries ago, colchicine has been discovered to inhibit many steps in the inflammatory process. The drug has good oral bioavailability and some enterohepatic recirculation, requiring dose adjustments for kidney disease and avoidance in liver disease. Toxicities are primarily gastrointestinal, hepatic, and hematologic. Colchicine is approved by the U.S. Federal Drug Administration for the treatment and prophylaxis of gout flares but has also been tried with varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 35 publications
0
38
0
2
Order By: Relevance
“…It is able to reduce neutrophil activity and migration by blocking microtubule assembly, phagocytosis and transport of MSU crystals, and reducing adhesion molecules on endothelial cells in response to IL-1 or TNF-a [46,74,75]. More recently, it has been demonstrated that colchicine also reduces NALP3 inflammasome-driven caspase-1 activation by microtubule inhibition which decreases MSU delivery [76].…”
Section: Treatment Of Acute Goutmentioning
confidence: 99%
“…It is able to reduce neutrophil activity and migration by blocking microtubule assembly, phagocytosis and transport of MSU crystals, and reducing adhesion molecules on endothelial cells in response to IL-1 or TNF-a [46,74,75]. More recently, it has been demonstrated that colchicine also reduces NALP3 inflammasome-driven caspase-1 activation by microtubule inhibition which decreases MSU delivery [76].…”
Section: Treatment Of Acute Goutmentioning
confidence: 99%
“…However colchicine can enter all tissues, it is lipophilic and quickly absorbed in the jejenum and ileum. Peak in plasma levels is obtained about two hours after oral administration [24,25]. In our study oral or intraperitoneal colchicine therapy did not provide any marked improvement on macroscopic and microscopic scores.…”
Section: Discussionmentioning
confidence: 45%
“…All authors recommend significant dose reductions in patients with glomerular filtration rate (GFR) <50 mL/min/1.73 m 2 . Some authors recommend complete avoidance of colchicine in patients with GFR <10 mL/ min/1.73 m 2 and patients undergoing hemodialysis [6,89] . However, these recommendations are not based on firm data.…”
Section: Concerns With Colchicine Use In Patients With Renal Functionmentioning
confidence: 99%